Academic freedom experiences among postdoctoral research fellows in South Africa: Implications for democratisation and transformation - Chiramba, O.; Nyoni, P. (South African Journal of Higher Education, 2025)
Academic freedom is a fundamental principle in higher education, but discussions about it often centre on faculty members and students, overlooking other groups like postdoctoral research fellows (PDRFs). This article combines empirical research and a review of literature to examine various aspects of academic freedom, including the institutional context and diverse university policies that shape PDRFs’ experiences. It focuses on how shifting power dynamics affect PDRFs and highlights the need to transform existing policies to create a more democratic academic environment. Drawing on Mamdani’s concept of unfreedom, the article critiques entrenched academic norms that stifle academic freedom for PDRFs. It explores the consequences of restricted academic freedom on the career development and intellectual growth of academics, particularly those in precarious positions like PDRFs. The findings uncover stereotypes and institutional practices that limit academic freedom, hinder transformation, and impede the democratisation process within post-apartheid universities. These practices not only constrain individual creativity and career progression but also diminish overall job satisfaction, especially for PDRFs. The study argues that many of these constraints originate from university bureaucracies and academic hierarchies, funding models, and power imbalances. It offers strategies for addressing these challenges and fostering a more inclusive academic environment. The article concludes by emphasising the importance of ensuring academic freedom for PDRFs and the role of collaboration between universities, research institutions, and funding bodies in promoting equitable power relations and clear expectations. This study calls for urgent reforms to enhance transformation and democratisation within universities, especially to protect the academic freedom of those in precarious positions like PDRFs. It advocates systemic changes to ensure that academic freedom is extended to all stakeholders.